Virtual Managers as Branding Tools - Nykolyshyn, S.; Khymytsia, N. (Visnyk Kharkivsʹkoï derz͡h︡avnoï akademiï kulʹtury, 2022)
The problems of the virtual manager as a tool for gaining trust in brands are studied, taking into account its capabilities. The functions and communication capabilities of chatbots are described. Based on the conducted survey, statistics were obtained on the growing role of virtual communication between brands and consumers of their products and services. The results of the survey showed that users prefer using chatbots in Telegram and Viber. It is justified that the growth of the role of virtual communication between brands and consumers of their products and services not only determines the demand for the introduction of chatbots in communication with the target audience, but also allows considering the chatbot as an important tool for building trust in the brand.